THE USE OF DIP LIGHTS IN WATER AS A FISH FISHING TOOL IN TRACING FISHING EQUIPMENT - Wahyu Fajar Ramadhan; Polaris Nasution; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstrakHandline fishing is a fishing gear that is widely used by fishermen in Lengayang District in Pesisir Selatan Regency, West Sumatra Province with a total of 245 fishing gear. The operation of handline fishing gear by fishermen in Lengayang District is usually assisted by FADs as a means of collecting fish and has never used a dip lamp in water as a fishing aid. To determine the effectiveness of the use of a dip lamp in water, it is necessary to compare the catches from hand line fishing gear with and without the use of a dip lamp in water where the dip lamp in water has a power of 50 watts. Of the three treatments, the highest catch was found in the operation of handlines using a dip lamp in 50 watts of water with a total catch of 23 fish compared to the catch from the operation of handline fishing equipment without the use of dipping lights in water with a total catch 15 tails Key word : Handline, fishing